Toponymy in the Mythology of the Kwadeware Sentani Community: Representation of Identity and Cultural Ecology - siswanto siswanto (Sabda: Jurnal Kajian Kebudayaan, 2026)
This study examined the mythological structure and toponymic origins among the Kwadeware people in the western region of Lake Sentani, Papua. Based on a collection of orally transmitted folktales, the research revealed that Kwadeware toponymy functioned not only as a geographical marker but also as a representation of cultural identity, ecological knowledge systems, and the cosmological history of the community. The myths of Ondoporo Kurare Pa Marweri, the migration from Unabo Toro, and the narratives of sacred stones, the spread of sago by Mangkung Borakoi, and the formation of villages such as Yonokhong, Dondai, Sosiri, Yakonde, and Doyo illustrated the integration among humans, nature, and spiritual forces. The findings demonstrated that Kwadeware toponymy preserved moral values, social structures, and a worldview that positioned nature as an integral part of spiritual life. The study concluded that in the modern context, preserving traditional toponymy was essential for maintaining cultural identity and local knowledge amid globalization pressures.Keywords: Kwadeware, mythology, toponymy, cultural identity, cultural ecology